An Eco-friendly and Mild Process for Deacetylation Reactions in Water - Bora, Utpal (Asian Journal of Chemistry, 2010)
A convenient methodology has been developed for the removal of a variety O-acetyl group in water. The reaction is promoted by sodium bicarbonate at room temperature. This method offers an efficient green alternative to the existing protocols since the reaction is preceded in water which is a cheap, non-toxic and non-volatile solvent.